Expanded Career Progression System: Public School Teachers’ Awareness, Engagement, and Aspiration on Career Development - Apale, Esmeralda (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined teachers’ awareness, engagement, and career aspirations under the Expanded Career Progression System (ECPS) among public elementary school teachers in Congressional District I of Bohol. Anchored on Social Cognitive Career Theory, the Theory of Planned Behavior, Herzberg’s Motivation-Hygiene Theory, and Systems Thinking, the study adopted a convergent parallel mixed-methods design to integrate quantitative and qualitative insights. Data were collected from 322 teachers through a structured questionnaire based on the Philippine Professional Standards for Teachers (PPST), while qualitative data were obtained from 10 purposively selected participants using open-ended responses and a clarificatory interview. Descriptive statistics and inferential analyses, including chi-square, t-test, ANOVA, and Spearman’s rho, were used for quantitative data, while thematic analysis following Braun and Clarke’s framework was applied to qualitative data. Findings revealed moderate levels of awareness and engagement but high levels of career aspirations. Awareness varied significantly by district, age, and length of service, while engagement differed by qualification level and aspirations by age. Significant positive relationships were found among awareness, engagement, and aspirations, indicating that improved understanding strengthens participation and motivation. Qualitative results highlighted documentation burdens, mentoring gaps, and resource constraints as key challenges, although ECPS was perceived to enhance reflective practice and professional growth. The study concludes that strengthening awareness, institutional support, and mentoring systems is essential for effective ECPS implementation. Recommendations include improving orientation, expanding access to professional development, and refining policy implementation to ensure equitable opportunities for teachers. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting teacher development, professional mobility, and effective policy implementation. It contributes to educational, institutional, and socio-economic sustainability by supporting equitable career progression, strengthening governance practices, and enhancing long-term teacher development systems within the education sector.